Pengaruh Neural Mobilization dan Manual Traction pada kasus Cervical Root Syndrome untuk Peningkatan Kemampuan Fungsional: A Case Report - Vira Silviana Ali; Totok Budi Santoso; Elif Nur Efendi (Jurnal Kesehatan dan Fisioterapi, 2022)
Abstract− Cervical Root Syndromeis a collection of symptoms in which the spinal nerves are compressedcontinuous process caused by the degeneration of the vertebrae and intervertebral discs in the neck region. The most common cause is a disturbance in the spinal nerve foramen due to a combination of several factors, namely decreased disc height and degenerative changes. In this case, the patient experienced cervical pain, limited Range of Motion (ROM), muscle weakness, pharesthesia, and decreased functional ability. The physiotherapy treatment given is Neural Mobilization and Manual Traction. This study uses the case report method which was carried out on Cervical Root Syndrome patients at the Praktik Fisioterapi Magetan in May 2022. This study aims to determine whether the administration of Neural Mobilization and Manual Traction has an effect on increasing functional ability in patients with Cervical Root Syndrome complaints. After being given the intervention in the form of Neural Mobilization and Manual Traction as much as 7 times, it was found a decrease in pain, an increase in Range Of Motion (ROM), an increase in muscle strength, a decrease in parasthesia and an increase in functional ability activity.Keywords: Cervical Root Syndrome, Neural Mobilization, Manual Traction, physiotherapy